A Multicopter Ground Testbed for the Evaluation of Attitude and Position Controller - Xuan-Mung, Nguyen; Hong, Sung-Kyung (International Journal of Engineering and Technology, 2018)
A ground testbed system to evaluate the performance of attitude and position control of multicopters is proposed in this paper. The system consists of a vehicle attached to a base via a sphere joint which allows the vehicle to rotate about the three axes roll, pitch and yaw. In addition, a pseudo positioning algorithm is presented to simulate the position of the vehicle based on a force sensor and an inertial measurement unit sensor. A global positioning system simulator is used to provide the artificial GPS signal based on the simulated position signal during the indoor trials. The proposed system provides the multicopters with all six degrees of freedom during flight allowing the vehicle to perform as if it were in actual flight. Several experimental flight tests are conducted to prove the effectiveness of the proposed system.Â